"An Ægyptian darknesse": pagan chronologies, historia sacra, and the hieroglyph in England, 1646-1690. Issue 1 (2nd January 2021) - Pope, Stephanie
ABSTRACT: In this article I consider the depiction of the Egyptian hieroglyph in several seventeenth-century English religio-historiographical works that engage with the problems posed by the Egyptian dynastic records – records that challenged the validity of biblical chronology. Critical tradition has been keen to view the hieroglyph in the context of esoteric European scholarship, while scholarship on the English Enlightenment has tended to overlook the importance of religious motivations in "secular" intellectual projects. I show here, however, that some of the first apparently "secular" approaches to the hieroglyphs in England were not in works that espoused proto-Enlightenment linguistics or other intellectual ideals, but in religiously-motivated projects that, seeking to buttress sacred history and the primacy of the Judaic tradition against the threat of pagan chronologies, aimed to discredit the hieroglyph as an icon of pagan learning.